Care Seeking Behavior For Pregnant and Women Giving Birth During the Covid-19 Pandemic - Rosdianah, Rosdianah; Mukarram, Yusril Ihsanul; Nurdin, Andi Armyn (Al-Sihah: The Public Health Science Journal, 2022)
The total number of maternal and child mortality in Indonesia annually has not yet reached the target set by World Health Organization. This figure is influenced by maternal compliance to perform antenatal care checks. The research aimed to investigate the behavior patterns of seeking help for pregnant and giving birth during the Covid-19 pandemic. The research design was observational with a cross-sectional study design. The population in this study was selected using the consecutive sampling method based on inclusion and exclusion criteria. Within this approach, 51 samples were obtained in Gowa Regency, to whom questionnaires were distributed to get further data. As seen from the research results, 50 samples (98%) performed antenatal care checks every month, while only 1 sample (2%) did not do antenatal care checks regularly every month. Regarding mothers’ knowledge of the Covid-19 pandemic, the data revealed that 33 samples had sufficient knowledge, 7 samples had good knowledge, and the rest, 11 samples, had less knowledge related to such a case. The pattern of care-seeking behavior of pregnant and giving-birth mothers during the pandemic has not changed from the period before the pandemic and pregnant women still routinely check their pregnancy every month.